Microbial Biosensors for Some Heavy Metal Ions - Singh, Jasminder (My University, 2014)
Whole cell microbes having phosphatase activity were identified for the preparation of biosensor using Pikovskaya media for bacterial culture and Beneck’s media for algal culture from the rhizospheric soil. Identified microbial colonies were tested for their phosphatase solubilizing capacity. Microbes having maximum solubilizing capacity were cultured and re-cultured using BG-11 inorganic media and were starved with respect to phosphate by suspending the media in phosphate free BG-11 media, before being used for immobilization on to the electrode surface. Starved microbes were immobilized on different electrode surfaces using bovine serum albumin (BSA) and were cross-linked with glutaraldehyde vapours for 30 minutes. The immobilized electrode was characterized for maximum output current by changing its cell density and optimum working environment by variation in pH of the solution. Immobilized electrode was also characterized for its composition, permeability and viability of the microbes in the membrane matrix with various techniques like scanning electron micrograph (SEM), cyclic voltammetry (CV) and spectrofluoremetry. Whole cell based amperometric biosensor was fabricated using an identified phosphatase solubilizing unicellular microalgae Chlorella sp. as the biocatalyst. The microbial culture was entrapped in a polymeric membrane of BSA directly interfaced to the surface of a platinum electrode for the detection of bioavailable heavy metal ions like zinc, copper, cadmium, cobalt and nickel. . The fabricated biosensor had a life time of 7 days and was found sensitive to a lower concentration level of 10−9 M of nickel ions, 10−10 M of cadmium and cobalt ions, 10−11 M of copper and zinc ions. The electrode system was workable in a detection range of 10-12 M to 10-6 M. The amperometric biosensor responds to heavy metal ions with a relative selectivity in the order: Zn2+ > Cu2+ > Cd2+ > Co2+ > Ni2+. A whole cell based biosensor was also prepared by immobilizing Chlorella sp. microbes over glassy carbon electrode with optimised composition of cell density. The electrode responds linearly in concentration range of 10-14 M to 10-6 M for zinc, copper, cadmium, cobalt and nickel ions. Relative selectivity of the metal ions can be ordered in following xiii sequence: Zn2+ >> Cu2+ ≈ Cd2+ > Co2+ > Ni2+. The biosensor had a life time of 14 days, after which, its analytical properties did not remain stable. Zinc dominates the inhibition of microbial activity over all other heavy metal ions selected for the study. With modified glassy carbon electrode cadmium and copper do not interfere with each other but these are inhibited in presence of zinc ions only. Prepared a whole cell based biosensor by immobilizing Chlorella sp. microbes having phosphatase activity over glassy carbon electrode. The electrode responds linearly in concentration range of 10−14 M to 10−6 M and lower detection limit of 10-14 M for mercury and showed its rare selectivity for mercury over other potential interferents like silver, alkali metals, alkaline earth metals and transition metals. The membrane electrode system had an expected life of 14 days. The biosensor was also tested for determination of mercury in a continuous flow system. A new assembly for online voltammetric determination was designed and used for the measurement of mercury ions which showed an excellent selectivity, sensitivity and reproducibility in a range of flow rate of 0.5 mL/min to 1.5 mL/min. The prepared biosensors were tested for their analytical applications in the determination of different heavy metal ions in real time samples collected from the laboratory drain and also those prepared artificially. The obtained results were compared with those obtained from atomic absorption spectrometer. Results of real time samples analyzed using flow system were compared with those by batch method and also with Atomic Absorption Spectroscopy (AAS).
PHD,SCBC
Keywords: biosensors; whole cell; amperometric; ultra sesitive